Obsessive measurement disorder or pragmatic bureaucracy? : coping with uncertainty in development aid relations - Alexius, Susanna; Vähämäki, Janet (Emerald Publishing Limited, 2024)
The ebook edition of this title is Open Access and freely available to read online. Complex coordination across time, space, and cultures involves a great deal of uncertainty. This uncertainty may be accepted and handled with judgment and pragmatism, but more often in contemporary modern society, it is treated as a technical problem to be 'solved'. This is a book about the paradoxical implications of the quest for certainty in interorganizational relations in the complex field of development aid. Authors Alexius and Vähämäki scrutinize questions related to the concept Obsessive Measurement Disorder, i.e. what causes an increase in control mechanisms, and how and when can this prove counterproductive? They further investigate the question on why performance management - and measurement requirements seem in some instances to hinder, and in others to support the implementation of aid projects and programs. Drawing on 80 original interviews with aid bureaucrats working at different levels and in different organizations, including public agencies, companies, non-government organisations, and universities all involved in development aid projects financed fully, or in part, by the Swedish taxpayer, they identify coping mechanisms and responses that may help to prevent the extremes of obsessive measurement disorder, and foster instead pragmatic, constructive organizing and learning that benefits not only aid organizations and their employees, but also - and more fundamentally - the societies in need.
Includes index.
Keywords: Bureaucracy.; Management.; Business & Economics -- Management.; Management and management techniques.; elektronické knihy; electronic books